Adalimumab dose escalation is effective for managing secondary loss of response in Crohn's disease. Issue 9 (3rd September 2014) - Ma, C.; Huang, V.; Fedorak, D. K.; Kroeker, K. I.; Dieleman, L. A.; Halloran, B. P.; Fedorak, R. N.
Summary Background The efficacy of adalimumab in maintaining remission in Crohn's disease patients may wane over time, leading to secondary loss of response that is often managed with dose escalation. However, the response to adalimumab dose escalation and long‐term outcomes after escalation have not been well evaluated. Aims To characterise the short‐ and long‐term clinical responses to adalimumab dose escalation for secondary loss of response. Methods A retrospective cohort study evaluating Crohn's disease out‐patients requiring adalimumab dose escalation for secondary loss of response from 2003 to 2013 was conducted. The primary outcome was the proportion of patients achieving symptomatic clinical response to dose escalation and subsequent development of tertiary loss of response. Duration of regained response was assessed by Kaplan–Meier analysis. Results Ninety‐two CD patients met inclusion criteria with mean duration of follow‐up of 170.2 weeks (±129.6 weeks). Disease distribution was predominantly ileal (37/92, 40.2%) or ileocolonic (43/92, 46.7%), with equal distribution of inflammatory (34.8%), stricturing (27.2%), and penetrating (38.0%) disease phenotypes. At 24 weeks post‐dose escalation, 74/92 (80.4%) patients had symptomatic clinical response. Among responders, median duration of sustained response was 69.2 weeks (IQR 29.4–107.1) but 42/74 (56.8%) responders experienced subsequent tertiary loss of response at a median time of 47.9 weeks (IQR 24.7–80.3). C‐reactive protein >10.0 mg/L at the time of dose escalation predicted tertiary loss of response in univariate analysis (OR 3.32, 95% CI: 1.18–9.37). Conclusions In patients with Crohn's disease, adalimumab dose escalation is effective for recapturing symptomatic response after secondary loss of response, but more than half will eventually experience a tertiary loss of response.